2015
DOI: 10.1371/journal.pone.0116092
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Glycolytic Enzymes, Mitochondrial Dysfunction and Increased Cytotoxicity in Glial Cells Treated with Alzheimer’s Disease Plasma

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder associated with increased oxidative stress and neuroinflammation. Markers of increased protein, lipid and nucleic acid oxidation and reduced activities of antioxidant enzymes have been reported in AD plasma. Amyloid plaques in the AD brain elicit a range of reactive inflammatory responses including complement activation and acute phase reactions, which may also be reflected in plasma. Previous studies have shown that human AD plasma may be cytotoxic to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 118 publications
8
15
0
Order By: Relevance
“…Valbuena et al verified the increase in glycolysis and TCA cycle was a result of poor adaptation to ROS generated in amyotrophic lateral sclerosis neuronal cells, and was a sign of neuronal death . Further, plasma from patients with Alzheimer's disease, a neurodegenerative disorder associated with increased oxidative stress, caused mitochondrial dysfunction and increased glycolysis as a compensatory action, ultimately leading to a loss of cell viability, as studied by Jayasena et al Therefore, our data may suggest that the delivery of TCM F1 and D1 moieties causes high oxidative stress leading to upregulation of glycolysis and the TCA cycle and may be the primary mechanism of toxicity observed with P1 and P2 conjugates. This also explains the three‐ to fivefold increase in oxidized glutathione (glutathione disulfide; GSSG) present in P1/P2‐treated cells (Figure , Panel B), which is normally upregulated to scavenge ROS .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Valbuena et al verified the increase in glycolysis and TCA cycle was a result of poor adaptation to ROS generated in amyotrophic lateral sclerosis neuronal cells, and was a sign of neuronal death . Further, plasma from patients with Alzheimer's disease, a neurodegenerative disorder associated with increased oxidative stress, caused mitochondrial dysfunction and increased glycolysis as a compensatory action, ultimately leading to a loss of cell viability, as studied by Jayasena et al Therefore, our data may suggest that the delivery of TCM F1 and D1 moieties causes high oxidative stress leading to upregulation of glycolysis and the TCA cycle and may be the primary mechanism of toxicity observed with P1 and P2 conjugates. This also explains the three‐ to fivefold increase in oxidized glutathione (glutathione disulfide; GSSG) present in P1/P2‐treated cells (Figure , Panel B), which is normally upregulated to scavenge ROS .…”
Section: Resultssupporting
confidence: 61%
“…We hypothesize that the increase in glycolysis is a response to oxidative stress caused by the generation of ROS, a primary mechanism of DOX and DOX‐metabolite toxicity . This is supported by several studies correlating increased glycolysis with oxidative stress and mitochondrial dysfunction . Wu and Wei in their work showed increased glycolytic flux was a result of oxidative stress in skin fibroblasts from patients with myoclonic epilepsy and ragged‐red fiber syndrome, in an attempt to generate NADH to help mitigate ROS generation .…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have shown that Aβ-plaques in the AD brain elicit inflammatory responses, which may also be reflected systemically in plasma. Treatment with AD plasma was found to affect cellular bioenergetics in a microglial cell line by upregulating glycolytic flux and enzyme expression arguably to compensate for mitochondrial dysfunction and decreased cell viability [107]. This observation supports the increasing body of evidence that inflammation and energy metabolism are closely linked phenomena in which microglial energetics may also have a significant contribution.…”
Section: Microglial Metabolism and Neurodegenerative Disorderssupporting
confidence: 72%
“…When existing neurons cannot take over lost ones, glucose metabolism begins to decline. Moreover, innate immune-mediated neuroinflammation also occurs in company with Aβ accumulation in AD, which often leads to abundant inflammatory cells, including glial activation that expresses high levels of glucose transporters and thus increases brain glycolytic activity [23,24,25]. Our study revealed the entorhinal cortex and hippocampus as regions affected first with glucose disorders, perhaps because these regions are highly dependent on the insulin signaling pathway and are initially subject to Aβ accumulation [26,27].…”
Section: Discussionmentioning
confidence: 99%